QUALITY OF SERVICE OF THE INDONESIA HEALTH CARD (KIS) PROGRAM AT GANDUS PUBLIC HOSPITAL, PALEMBANG CITY - Sisca Nopralia; Rendy Sueztra Canaldhy (Journal of Social and Economics Research, 2025)
The purpose of this study is to determine the quality of health services for Indonesian healthy card patients KIS at the Gandus regional general hospital. Increasing knowledge and providing an overview or contribution of thought to the development of administrative science, The method used in this study is the Qualitative method and the type of research is Descriptive. In this study, the theory used is the theory of Parasuraman et al (2005:78) who said that there are five dimensions of service quality, namely Responsiveness (responsiveness), Reliability (reliability), Assurance (guarantee), Empathy (empathy), and tangible (real). This study is included in the category of field research, using interview data collection methods, observation, and documentation in order to obtain valid data, This method is expected to add a detailed picture of how the research is studied, Data collection techniques such as observation, documentation, questionnaires, decision studies. The informants of this study were the head of outpatient administration, health workers, patient users.